Medulloid thyroid cancer - Estrugo, Roberto; Paperán (h), Juan A; Iraola, María; Toledo Correa, Nancy; Maggiolo, Jorge; Gregorio, Luis (Cirugía del Uruguay, 1977)
This series of seven cases of Medulloid Thyroid Cancer, has been taken from files of the "Mussio Fournier", Institute of Endocrinology and the Postgraduate Surgery Institute of the Pasteur Hospital in Montevideo. These tumors are derived from parafollicular cells. They are endocrinous adenomatosis because of their connection to other tumors and apudomas. Functionally, they are characterized by production of Calcytonine and other substances. They are often bilateral and a distinctive feature is the presence of cytoplasmatic granules and amyloid substances with positive dichroism. Its endocrinous syndrome, is characterized by diarrheas and eventually by skin reddening. Sone types run in families. Heredity is predominantly autosome. Pre-operatory diagnosis and postoperatory management consist of calcytonin dosage. The solo curative treatment is surgery which consist of total thyroidectomy. Sone aspects found in this series are worth stressing: -The amyloi. substance was present in all cases studied. -Were is high frequency of cervical and mediastinal metástasic adenopathies. -Diarrheas were found in 2 patients and they ceased after abscission of primitive tumor and its metastases. -Its evolution is slower than in the case of nondifferentiated cancers. In one case, appeared papillary and medular thyroid tumors in the same thyroid gland.